(untitled) (American Journal of Islam and Society, 1986)
This issue of the MISS introduces a format of five sections. The initial section, on Islamization of knowledge, consists of three articles. The first article was written by the late Lamya’ al-Faruqi, slain wife of al-Shahid Ismail al-Faruqi, who interprets the Islamization of knowledge through the sound arts. We hope her provocative analysis will trigger responses from our knowledgeable readers. The second paper, by the distinguished Pakistani scholar, Professor Akbar Ahmed, treats us to a lengthy analysis of anthropological knowledge from the perspective of the scholar interested in its Islamization. The third article in this section, by Professor Masudul Alam Choudhury, raises serious issues in the microeconomic foundations of Islamic economics. The second section is a symposium on political governance. It consists of some ’ijtihad by Muhammad Salahuddin on the limits of political obedience and a shorter account by Farhang Rajaee of the discrepancy between political ideal and reality in the little-researched Late-Classical period of Muslim history. Another symposium in the next issue, consisting of articles by Hasan Turabi and Muna Abdul-Fadl, covers the implications for change in societal institutions and in the ’Ummah generally. The middle section of this issue is a position paper by Sayeed al Seini, who gives us his interpretation of the Islamic concept of news. This area of research is beginning to occupy the attention of Muslim students of communications, and we hope more papers will be published in future issues. The fourth section consists of two research notes. The first one, by Professor Mushtaqur Rahman, looks at the Afghan conflict and analyses the way it may affect the future of Central Asian Muslims in the “pivot of Asia” during the 1980’s and beyond. This issue is of great concern to all Muslims around the world. The second note, by Hasan A. Yahya, examines the conflict of secularization and tradition, especially as it affects women, reflected in reading textbooks in Jordan, Libya, Saudi Arabia, and Syria. Using content analysis, the author identifies the main factors that in his opinion are responsible for this development. The final section, of literature reviews, starts with an article by Muhammad Benaboud on Orientalist treatment of Revelation and the Prophet’s Sira, some of which has made some constructive contribution to the study of the Muslim world. professor Benaboud’s paper may encourage others to scrutinize closely contemporary Orientalist scholarship, in order to counter disinformation and to develop Islamic leadership in the study of comparative religion ...